PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. MITRA KARYA SURYA KENCANA DI PONTIANAK KALIMANTAN BARAT - Gusnita, Gusnita (STIE 'INDONESIA' Pontianak, 2024)
This study entitled The Influence of Organizational Culture on Employee Performance at PT Mitra Karya Surya Kencana in Pontianak, West Kalimantan. A good organizational culture can be a driving force for employee performance, this can also have an impact on good performance results from employees and can help companies reach their goals. The problem raised is whether there is an influence of organizational culture on employee performance at PT. Mitra Karya Surya Kencana in Pontianak, West Kalimantan. There are two variables in this study, namely organizational culture which is the independent variable and employee performance as the dependent variable. The population in this study were 33 people, namely all employees at PT. Mitra Karya Surya Kencana in Pontianak, West Kalimantan. The results obtained in this study are that organizational culture has a significant influence on employee performance at PT. Mitra Karya Surya Kencana in Pontianak, West Kalimantan, which can be seen from the results of the t test and based on the value of the coefficient of determination (R2).